The Dynamics of Tafsir in the Digital Age: Opportunities and Challenges - Nikmatul Khairiyah; Putri, Mirna; Misbah, Misbah; Afifa, Afifa; Bin Alias, Muhammad Firdaus; Wulandari, Ratna (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
The development of digital technology has brought significant changes to the world of Quranic tafsir. This transformation has not only affected distribution and accessibility, but also influenced the authority, methods, and forms of tafsir itself. This study aims to analyze the dynamics of tafsir in the digital age by highlighting three main aspects: changes in the form and patterns of tafsir, the role of digital media in the dissemination of tafsir, and the positive opportunities arising from this phenomenon. The method used is a literature review with a qualitative-descriptive approach. The results of the study show that digital media has played a major role in democratizing access to tafsir, expanding the scope of Islamic themes, and providing a new space for more open religious discourse. However, these dynamics also present serious challenges such as a crisis of scientific authority, the spread of tafsir without scientific validation, and the risk of polarization due to social media algorithms. These findings underscore the importance of Islamic digital literacy and the active role of religious institutions in guiding responsible tafsir practices in the digital age.